2017
DOI: 10.1038/pr.2017.26
|View full text |Cite
|
Sign up to set email alerts
|

Continuous capnography monitoring during resuscitation in a transitional large mammalian model of asphyxial cardiac arrest

Abstract: BACKGROUND In neonates requiring chest compression (CC) during resuscitation, neonatal resuscitation program (NRP) recommends against relying on a single feedback device such as end-tidal carbon dioxide (ETCO2) or saturations (SpO2) to determine return of spontaneous circulation (ROSC) until more evidence becomes available. METHODS We evaluated the role of monitoring ETCO2 during resuscitation in a lamb model of cardiac arrest induced by umbilical cord occlusion (n = 21). Lambs were resuscitated as per NRP g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Moreover, quality of CPR provided was monitored using defibrillator with CPR quality analysis features and no other direct or invasive measurements of CPR quality was measured. In regard to EtCO 2, a recent study using a lamb asphyxial cardiac arrest model, Chandrasekharan et al demonstrated a relationship between EtCO 2 and adequate chest compression during resuscitation, and concluded that a rapid increase in EtCO 2 with a threshold of > 32 mmHg is 100 sensitive and 97% specific in predicting ROSC [29]. Moreover, a recent multicenter study of 583 adult patients with in-and out hospital CA showed that depth of chest compression was associated with higher EtCO 2 which suggest that EtCO 2 monitoring during CPR might be a useful tool to guide effective resuscitation after CA [30].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, quality of CPR provided was monitored using defibrillator with CPR quality analysis features and no other direct or invasive measurements of CPR quality was measured. In regard to EtCO 2, a recent study using a lamb asphyxial cardiac arrest model, Chandrasekharan et al demonstrated a relationship between EtCO 2 and adequate chest compression during resuscitation, and concluded that a rapid increase in EtCO 2 with a threshold of > 32 mmHg is 100 sensitive and 97% specific in predicting ROSC [29]. Moreover, a recent multicenter study of 583 adult patients with in-and out hospital CA showed that depth of chest compression was associated with higher EtCO 2 which suggest that EtCO 2 monitoring during CPR might be a useful tool to guide effective resuscitation after CA [30].…”
Section: Discussionmentioning
confidence: 99%
“…They were intubated with a 10.0 mm-cuffed endotracheal tube (ETT) and ventilated with 21% oxygen and 2–3% isoflurane at 16 breaths/min. The ewes were continuously monitored with a pulse oximeter and an end-tidal CO 2 (EtCO 2 ) monitor [9,10]. Following cesarean section, fetal lambs were partially exteriorized and intubated with a 4.5 mm-cuffed ETT as previously described [11].…”
Section: Methodsmentioning
confidence: 99%
“…Use of 100% oxygen is the current recommendation for ventilation during CC until the end of resuscitation or return of spontaneous circulation (ROSC), although the efficacy of this practice still needs evidence [28,29,30]. Research in CC during neonatal resuscitation has so far focused on different techniques of compression, depth of CC, use of sustained inflations, asynchronous ventilation, oxygen concentrations, and use of assisted devices to predict effective CC and ROSC [1,27,31,32,33,34]. The current recommendation to initiate CC for HR < 60/min during resuscitation is probably based on consensus rather than clear evidence.…”
Section: Discussionmentioning
confidence: 99%